Relational Resilience and Exclusive Breastfeeding Among Fishing Couples: A Dyadic Study in Families with Stunted Children, Donggala - Sahrul; Muhammad Syafar; Suriah; A. Arsunan Arsin; Nurzakiah; Khairunnisaa; Nur Mila Sari (Media Gizi Indonesia, 2026)
Among fishing families with stunted children in coastal areas, exclusive breastfeeding occurs within intergenerational feeding norms, economic vulnerability, and limited paternal involvement. This study explored relational resilience strategies developed by fishing couples to sustain breastfeeding practices amid child stunting. A qualitative dyadic phenomenological design guided by Walsh's Family Resilience Framework was employed. Data were collected from 35 participants: 10 husband-wife dyads, five community leaders, and 10 extended family members, through individual and joint in-depth interviews and focus group discussions. Data were analyzed iteratively through within-participant, within-dyad, and cross-dyad comparisons to identify relational patterns and develop an empirically derived typology of relational resilience. Findings showed that couples experienced overlapping emotional, cultural, and structural shocks, including pressure to provide prelacteal feeding and reduced paternal involvement due to fishing-related work. Most dyads demonstrated moderate resilience, characterized by emotional solidarity, silent empathy, and adaptive compromise, often prioritizing family harmony over resistance to intergenerational norms, resulting in early supplementation and incomplete exclusive breastfeeding. Relational resilience functioned as a dyadic process maintaining emotional cohesion and caregiving continuity rather than strict adherence to breastfeeding recommendations. Strengthening breastfeeding sustainability in coastal settings requires culturally responsive, family-centered interventions engaging fathers and extended kin.